An Unambiguous Distance-Based MIQP Model to Solve Economic Dispatch Problems with Disjoint Operating Zones - Pourakbari-Kasmaei, Mahdi [UNESP] (2016)
This letter presents an unambiguous distance-based mixed-integer quadratic programming (UDB-MIQP) model to solve economic dispatch problems with disjoint operating zones. By considering the distances among the prohibited zones, the unnecessary variables will be eliminated and, consequently, a significant decrease, both in terms of variables and constraints, is obtained. The results show that the UDB model compared to existing MIQP models in the literature can achieve the global optimal solution with a significantly reduced problem complexity, both in terms of variables and constraints. In addition, the results indicate the superiority of the method in computational time reduction.